Faktor-Faktor Kunci Kesuksesan Implementasi Manajemen Pengetahuan pada PT Unilever Indonesia Tbk. - Windarti, Windarti; Sukmawati, Anggraini (IPB University, 2011)
Social environment provides organization capability in knowledge creation, transfer and implementation which leading the company into successful knowledge management by providing competitive human capital. PT. Unilever Indonesia, Tbk as successful Indonesian company in Knowledge Management was awarded the Most Admired Knowledge Enterprise (MAKE) in Asia from 2005 until 2009. The study objectives are 1) to identify knowledge management implementation 2) to analyze the gap between perceived and actual implementation factors in knowledge management 3) to analyze social environment success factor in knowledge management implementation. The primary data collection methods were using questionnaires from 86 respondents and in depth interview with Learning Specialist of PT. Unilever Indonesia, Tbk, and secondary data were collected from journals, books, company annual year reports and other related literatures. There were five knowledge management implementation approaches used by the company: human resources development, learning environment as a culture, stakeholders’ knowledge as one of resources, community education and supported infrastructure and facilities. Statistical analysis showed there is no gap between perceived and actual implementation factors in knowledge management. And trust, autonomy, involvement and empowerment were the social environment key success factors in knowledge management implementation.